2006
DOI: 10.1139/f06-127
|View full text |Cite
|
Sign up to set email alerts
|

Altered growth and related physiological responses in juvenile Chinook salmon (Oncorhynchus tshawytscha) from dietary exposure to polycyclic aromatic hydrocarbons (PAHs)

Abstract: A dietary feeding study with polycyclic aromatic hydrocarbons (PAHs) was conducted with juvenile Chinook salmon (Oncorhynchus tshawytscha) to mimic exposure from urban estuaries during their transition from freshwater to seawater. A significant reduction in mean fish dry weight was observed only for the highest doses; however, analysis of variance (ANOVA) using standard deviations and examination of the cumulative frequency plots revealed high variability among all treatments. The skewed fish weight distributi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
73
0
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(86 citation statements)
references
References 28 publications
5
73
0
4
Order By: Relevance
“…As lipid reserve in control juvenile appeared especially high with regards to in situ measurments in adjacent coastal nurseries, the exposed juvenile presented and TAG:ST ratios dramatically lower than in situ observed minimum (Durieux et al 2007). A similar, toxicant-induced starvation associated with reduced growth and lipid content was also found in juvenile Chinook salmon (Oncorhynchus tshawytscha) fed PAH-contaminated food (Meador et al 2006). …”
Section: Reduced Biological Performances At Individual Levelmentioning
confidence: 61%
“…As lipid reserve in control juvenile appeared especially high with regards to in situ measurments in adjacent coastal nurseries, the exposed juvenile presented and TAG:ST ratios dramatically lower than in situ observed minimum (Durieux et al 2007). A similar, toxicant-induced starvation associated with reduced growth and lipid content was also found in juvenile Chinook salmon (Oncorhynchus tshawytscha) fed PAH-contaminated food (Meador et al 2006). …”
Section: Reduced Biological Performances At Individual Levelmentioning
confidence: 61%
“…However, only a few studies have investigated the toxicity of dietary PAHs to fish when fed contaminated feed over a longer period. One study reported a reduction in weight in juvenile Chinook salmon (Oncorhynchus tshawytscha) fed a mixture of 21 PAHs (22 µg/g fish ww/day) for 54 days (Meador et al, 2006), while no effect on growth was seen in juvenile grouper (Epinephelus aerolatus) fed BaP (12.5 µg/g fish ww/day) for 4 weeks .…”
Section: Polyaromatic Hydrocarbons (Pahs)mentioning
confidence: 99%
“…pierścieniowych węglowodorów aromatycznych do środowiska należy wymienić: pożary lasów i erupcje wulkanów [17,20].…”
unclassified
“…Występowanie WWA w żywności jest spowodowane głównie zanieczyszczeniem środowiska i niektórymi technologicznymi procesami utrwalania żywności, jak wędze-nie, smażenie lub grillowanie [17,20]. Badania zawartości WWA w produktach poddanych takim obróbkom informują o poziomie zanieczyszczenia tymi związkami w poszczególnych grupach wyrobów mięsnych [2,7,16].…”
unclassified
See 1 more Smart Citation